Performance Optimization of Coal Hauling Operations Through DMAIC Framework: A Case Study at PT Berau Coal - Paseru, Alvito Tirano; Yudoko, Gatot; Sanusi, Dudu Anwar; Ardiansyah, Pandu Zea; Limowa, Agung (Journal Integration of Management Studies, 2025)
The coal mining industry faces increasing demands to enhance operational efficiency and reduce costs in order to remain competitive amid dynamic market conditions. This research aims to optimize the coal hauling process at PT Berau Coal, one of Indonesia's major coal producers, by applying the Lean Six Sigma methodology using the DMAIC (Define, Measure, Analyze, Improve, Control) framework. A combination of quantitative and qualitative data collection methods, including process mapping, root cause analysis, and productivity measurement, is employed to systematically identify inefficiencies and bottlenecks within the coal hauling operation in Binungan Mine Operation Block 8. Research shows that significant productivity losses are attributed to prolonged waiting times, process delays, and insufficient standard operating procedures (SOPs). To address these issues, a set of improvement strategies has been formulated, emphasizing the renewal and enforcement of Standard Operating Procedures (SOPs), the implementation of a Fleet Management System (FMS) for real-time monitoring and decision-making, and the application of simulation modeling using AnyLogic software to assess the effectiveness of the suggested changes. Importantly, simulation results demonstrate that the average number of cycles per productive hour can increase from 5–6 to 9 cycles per hour through optimized operations. The findings demonstrate that implementing Lean Six Sigma within the DMAIC framework can substantially enhance coal hauling productivity, reduce operational cycle times, and improve overall cost efficiency. This research provides a framework for ongoing improvement in mining logistics and offers actionable insights for practitioners seeking sustainable operational excellence in a competitive industry.